2004
DOI: 10.1590/s1677-55382004000100006
|View full text |Cite
|
Sign up to set email alerts
|

Urolithiasis associated with topiramate

Abstract: Objective: Topiramate is a sulfamate-substituted monosaccharide anticonvulsant used as adjunctive therapy for intractable refractory seizures. It is report a case of topiramate-induced urolithiasis.Case Report: A 35-year-old man presented with acute, right-sided, colicky flank pain. He denied hematuria or dysuria. He was in use of phenytoin, risperidone, phenobarbital, and topiramate. The total daily dose of topiramate was 375 mg. A CT scan showed a 7 x 1 mm curvilinear density at the right ureterovesical junc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…Our study corroborates the same, showing a linear decrease in urinary citrate with time and dose of topiramate which was similar to the study published by Warner BW et al [8] Notably in our study, the stone analysis showed a predominance of Calcium Phosphate in four patients where the stone analysis was done. The same has been shown in other studies as well [9,10] . Topiramate was earlier believed to cause urolithiasis by a similar mechanism as in Type 1 Renal Tubular Acidosis, by inhibiting Carbonic anhydrase at proximal tubule.…”
Section: Discussionsupporting
confidence: 91%
“…Our study corroborates the same, showing a linear decrease in urinary citrate with time and dose of topiramate which was similar to the study published by Warner BW et al [8] Notably in our study, the stone analysis showed a predominance of Calcium Phosphate in four patients where the stone analysis was done. The same has been shown in other studies as well [9,10] . Topiramate was earlier believed to cause urolithiasis by a similar mechanism as in Type 1 Renal Tubular Acidosis, by inhibiting Carbonic anhydrase at proximal tubule.…”
Section: Discussionsupporting
confidence: 91%
“…The development of urolithiasis can be summarized in three pathways [12]: overgrowth on interstitial apatite plaque such as idiopathic calcium oxalate stone, crystal deposits in renal tubules, and free solution crystallization such as cystinuria or hyperoxaluria. Overgrowth on interstitial apatite plaque may be the pathway responsible for the development of urolithiasis in patients receiving topiramate [5,10,[12][13][14][15][16]. In the pathway, the increased urinary oxalate [8,11,14] may deposit on the plaque and increase the sizes of the stones.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer (PCa) represents the most frequent solid cancer in males, and it continues to be the primary cause of cancer‐related death in these groups 1,2 . Comprehensive multi‐omics investigations, including genomic, transcriptomic, epigenomic, and proteomic analyses, have been undertaken in the last few years to better understand the heterogeneity of this malignancy 3–6 .…”
Section: Introductionmentioning
confidence: 99%